2004
DOI: 10.1094/mpmi.2004.17.6.577
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Characterization of Victorin Sensitivity in Arabidopsis thaliana

Abstract: Cochliobolus victoriae is a necrotrophic fungus that produces a host-selective toxin called victorin. Victorin is considered to be host selective because it has been known to affect only certain allohexaploid oat cultivars containing the dominant Vb gene. Oat cultivars containing Vb are also the only genotypes susceptible to C. victoriae. Assays were developed to screen the "nonhost" plant of C. victoriae, Arabidopsis thaliana, for victorin sensitivity. Sensitivity to victorin was identified in six of 433 bulk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
49
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(49 citation statements)
references
References 25 publications
0
49
0
Order By: Relevance
“…Col-4, Ws, and mutant lines, jar1-1 (39), npr1-1 (40), ein2-1 (41), pad3 (42), and NahG (23), all in Col-0, were obtained from the Ohio State University Arabidopsis Biological Resource Center (Columbus, OH). LOV1 (16) and Col-LOV (36) were generated in our laboratory. Other seeds were obtained from the following individuals: Sainsbury Laboratory [eds1-1 Ws (43) (24)], and J. Chang [rar1-1 (25)].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Col-4, Ws, and mutant lines, jar1-1 (39), npr1-1 (40), ein2-1 (41), pad3 (42), and NahG (23), all in Col-0, were obtained from the Ohio State University Arabidopsis Biological Resource Center (Columbus, OH). LOV1 (16) and Col-LOV (36) were generated in our laboratory. Other seeds were obtained from the following individuals: Sainsbury Laboratory [eds1-1 Ws (43) (24)], and J. Chang [rar1-1 (25)].…”
Section: Methodsmentioning
confidence: 99%
“…A locus conferring disease susceptibility to C. victoriae in Arabidopsis, called LOV1, was mapped to the interval between Nga63 and NCCI on Chromosome 1 (16). We fine-mapped LOV1, using an additional 200 victorininsensitive F 2 progeny of a cross between a victorin-sensitive line, LOV1 (ecotype Cl-0), and victorin-insensitive Col-4.…”
Section: Rpp8 Resistance Gene Familymentioning
confidence: 99%
See 2 more Smart Citations
“…This data confirmed that elevated expression of GRX and TRX genes contribute to the enhanced susceptibility of the med18 and yy1 mutants to fungal infection. Arabidopsis grxs13 mutant exhibits enhanced resistance to B. cinerea 26 , whereas the trx-h5 mutant is insensitive to the victorin toxin produced by the necrotrophic fungus Cochliobolus victoriae 27 . Interestingly, TRX-h5 is a direct virulence target for the victorin toxin 28 .…”
Section: Med18 Contributes To Plant Defence Against Necrotrophsmentioning
confidence: 99%